Optimizing plant density for fiber and seed production in industrial hemp (Cannabis sativa L.) - Levent Yazici (Journal of King Saud University: Science, 2023)
Background: Industrial hemp (Cannabis sativa L.) is rated among the important green fibers and planting density significantly alters its fiber and seed production. However, optimum planting density is unknown for different cultivars available in Turkey. Methods: This study determined the effects of four planting densities (i.e., 100, 150, 200, and 250 plants m−2) on yield and quality traits of local ‘Narlısaray’ population and ‘Futura 75′ industrial hemp cultivar. Results: Planting density significantly altered the yield and fiber production. The ‘Narlısaray’ population recorded higher values for plant height, technical stem length, stem diameter, biomass yield, dry stem weight, and fiber yield. In contrast, seed yield, fiber rate, and oil rate were higher in ‘Futura 75′ cultivar. According to the average data of two years, plant height varied from 183.1 to 202.4 cm, technical stem length ranged from 130.8 to 151.3 cm, stem diameter 7.2–10.2 mm, fresh biomass 16400.3–22790.3 kg ha−1, stem dry weight 6730.8–9290.8 kg ha−1, fiber yield 1820.9–2610.9 kg ha−1, seed yield was 820.8–940.8 kh da-1, fiber ratio 27.7–30.3 %, and oil ratio was 28.5–31.1 %. Conclusion: The two-season average evaluation showed that the most appropriate planting density was 150 plant m−2 of hemp under ecological conditions of Yozgat province, Turkey.